Analysis of maternal mortality: a retrospective study at tertiary care centre - Khandale, Surekha N.; Kedar, Kshama (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Mother is the pillar of the family and maternal deaths during pregnancy and delivery are great loss to baby, family, society and country too. Epidemiological data pertaining to maternal mortality is valuable in each set-up to design interventional programs to reduce the ratio favourably. This study was design to evaluate the mortality rate in our hospital, to assess the epidemiological aspects and causes of maternal mortality, types of delay, and to suggest recommendations for improvement. Aim of the study was to analyse the causes of maternal death at tertiary care centre. Objective of the study was to analyse causes of maternal death and type of delay, and to suggest measures to reduce it. Methods: A retrospective study done at a tertiary level care centre from January 2011 to June15. Demographic data and other data were collected from maternal death review forms and case records. Data studied and analysed. Results: Most maternal deaths were due to obstetric causes like eclampsia (16.66%), preeclampsia (11.53%), anaemia (14.10%)and haemorrhage (10.25%). Associated co-morbid medical conditions hepatitis (6.41%) and heart disease (5.12%) were in the top list. Majority women were from rural area (69.23%), belonged to below poverty line (76.92%), had less than three visits (64.09%), received care at periphery below the level of specialist sub-district hospital. 94.87%were referred, and travelled more than 4 hours to reach hospital (88.44%). In majority cases Type 1 delay was most common (85.89%) comparatively to Type 2 and 3 delay. Conclusions: High risk cases should be identified. Early referral, easy transport, continued skill based training, monitoring of health services can reduce maternal mortality. Special training should be conducted for ASHA workers and ANM who generally works at grass root level in our country. Continued medical training is required for medical officers who are working at PHC and sub district hospital for early recognition of high risk women and their referral in time to higher centers to avoid maternal near miss or death.